Lycium barbarum Glycopeptide Alleviates Neomycin‐Induced Ototoxicity by Inhibiting Tryptophan Hydroxylase‐Mediated Serotonin Biosynthesis - Yunhao Wu; Li Zhang; Shengda Cao; Jingwen Zhang; Cheng Li; Yunlong Shan; Qiuping Liu; Zhexiong Yu; Qiaojun Fang; Yuhua Zhang; Xiaolong Fu; Kwok‐Fai So; et al. (Advanced Science)
Abstract Aminoglycoside antibiotic‐induced sensorineural hearing loss (SNHL) is a common sensory disorder that requires the development of prophylactic and therapeutic interventions. Lycium barbarum glycopeptide (LBGP) is a peptidoglycan isolated and purified from Lycium barbarum polysaccharides that exhibit significant anti‐inflammatory, antioxidant, and neuroprotective effects, but the role of LBGP in aminoglycoside‐induced SNHL has not been well investigated. Here it is shown that LBGP can protect against neomycin‐induced hearing impairment and alleviate oxidative stress in a neomycin‐induced SNHL mouse model. Moreover, it is further found that inhibition of tryptophan hydroxylase (Tph)‐mediated serotonin (5‐HT) biosynthesis plays a key role in the mechanism of action of LBGP in treating neomycin‐induced hearing loss. Systemic delivery of 5‐HT increased neomycin‐induced apoptosis of cochlear hair cells and spiral ganglion neurons, and pharmacological Tph2 inhibition with P‐chlorophenylalanine or Tph2 knock down by AAV‐ie‐Tph2 effectively attenuated neomycin‐induced hearing dysfunction. Collectively, these results provide a promising strategy for the prevention of SNHL by using natural plant extract which is more available and exhibits lower side effects compared with other otoprotective drugs, and identify Tph2 as a potential pharmacological target for the treatment of aminoglycoside‐induced ototoxicity.